Spatial Policy Tools. The Space as a Public Good - Pawel MICKIEWICZ; Maciej NOWAK; Bartosz MICKIEWICZ (Communications of International Proceedings, 2020)
This paper defines the roles of spatial policy tools protecting the space understood as a public good. Space protection in this approach must be implemented through specific spatial policy tools. The paper verifies the real scope of such protection. An attempt was made to translate approaches and dilemmas regarding public goods into conditions related to the spatial management system.
Keywords: Public Goods; Space; Spatial Order; Planning and Spatial Development.